Hypothalamus in Health and Diseases - Baloyannis, Stavros J.; Oxholm Gordeladze, Jan (IntechOpen, 2018)
The human hypothalamus, a small structure at the base of the brain, has strategic importance for the harmonic function of the human body. It controls the autonomic nervous system, neuroendocrine function, circadian and circannual rhythms, somatic activities, and behavior, and is situated at the borders between the brain and the body and the brain and the soul, meeting points for mind and body. The hypothalamus is involved in a wide range of higher mental functions, including attention, learning and reinforcement of mnemonic processes, emotional control, mood stability, and cognitive-emotional interactions. It also has a role to play in behavioral disorders, panic reactions, cluster headache, gelastic epilepsy, mental deficiency, periodic disorders, depression, autism, and schizophrenia, and in a substantial number of neurodegenerative diseases. It enlarges greatly the dimensions of the hypothalamic contribution in controlling psychosomatic equilibrium and retaining internal unity of the human existence.